Safety of child passengers who ride to school on a motorcycle: An observational study in two Argentine cities. (July 2021) - Tosi, Jeremías David; Poó, Fernando Martín; Ledesma, Ruben Daniel; Firsenko, Ekaterina
Abstract: In low- and middle-income countries, the motorcycle has increasingly become a means of family transportation due to its low cost and the poor quality of public transportation. Consequently, many child motorcycle passengers are at an elevated risk of serious injury in the event of a traffic crash. The available research on child safety devices is scarce and focused mainly on helmet use, while other devices (e.g. high-visibility clothing) have received little attention. This observational study documented the safety conditions and related factors of primary schoolchildren who rode to school as motorcycle passengers in two cities of Argentina. Data was obtained in the vicinity of 27 public primary schools in two cities of Argentina (one mid-sized city and the other a small city by the country's standards) between May 2018 and September 2019. A total of 1440 motorcycle occupants (656 drivers and 784 child passengers) were observed. The use of an adequate helmet was lower among children (vs. drivers). Most of the children were unable to reach the motorcycle's footrests, did not use high-visibility clothing or a fastening device, carried a backpack, and mounted and dismounted the motorcycle in an unsafe place. Some children rode in front of the driver or in a motorcycle with three or four occupants. Use of helmet by drivers and driver sex (woman) were related with an increase in safety in children. The indicators were worse in the larger city. The results revealed a low level of adoption of safety measures in children as well as in adults in both cities. This suggests that motorcycle travel is unsafe. Greater effort is needed to improve motorcycle safety, especially for children. It is important to debate regulatory details such as a minimum age for passengers, a limit on the number of passengers, and other safety criteria. It is also important to conduct educational campaigns that include the distribution of safety devices. Highlights: The results revealed a low level of adoption for safety measures in children as well as in adults. The frequency of helmet use was lower among children (vs. drivers). The adoption of other safety measures was also relatively low (e.g. high-visibility clothing, fastening devices, footrests, seating position). Child safety conditions were associated with those of the other motorcycle occupants. Motorcycle type and license plate were a factor associated with the presence of a number of safety measures. The indicators were worse in the larger city.